Slave owners of West Africa: decision making in the age of abolition - Greene, Sandra E. (Indiana University Press, 2017)
Amegashie Afeku of Keta: priest, political advisor, businessman, slave owner -- Nyaho Tamakloe of Anlo: of chieftaincy and slavery, of politics and the personal -- Noah Yawo of Ho-Kpenoe: the faith journey of a slave owner